The speed control of DC servo motor with proportional integral, fuzzy logic and adaptive neuro-fuzzy inference systems - (:unkn) unknown (WORLD SCIENTIFIC AND ENGINEERING ACAD AND SOC, 2007)
In this study DC servo motor's mathematical model and equations were extracted for solving the speed control problem. There were three different methods used for controlling the speed. It was created simulation model at the Matlab programme and implemented proportional-integral, fuzzy and adaptive neuro fuzzy inference system controllers respectively while it was working variable conditions. At the servo motor application it is expected that no overshoot, settling reference value quickly and minimum influence on the system stability.
Keywords: DC servo motor; proportional-integral; fuzzy; adaptive neuro fuzzy inference system